Development of a Mathematics Module Based on The Huma Betang Context for Teaching Polyhedra - Putri Sasalia; Sry Rita Puspitasari; Demitra Demitra; Loy Cindy Br. Milala (Didaktik Matematika, 2025)
Abstract. The teaching module is a very important component in the learning process. A good teaching module will affect the learning process and results of students. A teaching module that provides a real context in accordance with the lives of students makes the learning process more meaningful. The real context raised in this study is the DAS, where rivers are the main natural resources for the people of Kalimantan, especially Central Kalimantan. Therefore, the researcher aims to develop a junior high school mathematics teaching module based on RME in the watershed environment. The research method uses a development method with the Dick Carey model, namely (1) Identify Instructional Goal, (2) Conduct Instructional Analysis; (3) Analyze Learners and Contexts; (4) Write Performance Objectives; (5) Develop Assessment Instruments; (6) Develop Instructional Strategy; (7) Develop and Select Instructional Materials; (8) Design and Conduct Formative Evaluation of Instruction; (9) Revise Instruction; (10) Design and Conduct Summative. The results of the study from the first to the seventh stages were obtained from three experts, namely the teaching module in the aspect of element quality obtained a high level of validity of 95%. The aspect of the characteristic module and the aspect of language obtained the same percentage, namely 85% high validity. The last aspect, PBL RME aspect, obtained a high level of validity of 88%. While in the Design and Conduct Formative Evaluation of Instruction, Revise Instruction, and Design and Conduct Summative stages, it was obtained from the results of 150 junior high school student responses, namely the response of students to the learning process using the flat-sided spatial geometry teaching module based on RME in the DAS environment, namely 62 out of 150 students or 41.3% of all students said that the teaching module obtained a fairly good category.